2021
DOI: 10.1088/1361-6463/ac0de5
|View full text |Cite
|
Sign up to set email alerts
|

Critical-dimension scanning electron microscope characterization of smoothly varying wave structures with a Monte Carlo simulation

Abstract: Scanning electron microscopy (SEM) characterization of a smoothly varying nanograting structure (a Pt-coated Cr grid on a Si substrate) with a sinusoidal waveform has been carried out by a Monte Carlo (MC) simulation technique. Previous studies with critical-dimension (CD) SEM (CD-SEM) have mostly concerned line structures with sharp edges so that there is an obvious edge bloom in the linescan profile of secondary electrons. In contrast, the present grating structures prepared by a laser-focused atomic deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Zou et al [18] have further studied the MBL method to include those parameters considered later in ISO 21466; for example, the beam-sample interaction model contains two effective parameters, namely, the line material and substrate material. Khan et al [32] applied the MBL method to characterize more complex sample structures having a smooth waveform and with a coated film, and we [33] have further extended the application of the method to rather more complex grating lines in 3D morphology and material components or electronic structure. Villarrubia et al [34] confirmed that the MBL method can be applied to linewidth measurements down to 10 nm scale; the measurements were in good agreement with the direct observation by a transmission electron microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al [18] have further studied the MBL method to include those parameters considered later in ISO 21466; for example, the beam-sample interaction model contains two effective parameters, namely, the line material and substrate material. Khan et al [32] applied the MBL method to characterize more complex sample structures having a smooth waveform and with a coated film, and we [33] have further extended the application of the method to rather more complex grating lines in 3D morphology and material components or electronic structure. Villarrubia et al [34] confirmed that the MBL method can be applied to linewidth measurements down to 10 nm scale; the measurements were in good agreement with the direct observation by a transmission electron microscope.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Cr grating directly formed by laser-focused atom deposition in a standing wave has a smooth wave-like line shape. In our previous study, the SEM characterization of a Cr grating having a multilayer structure (Pt layer covering the Cr line on a Si substrate) was successfully performed with a Monte Carlo-simulated MBL database [46]. Unlike a sharp-edged trapezoidal line structure, the SEM linescan profile of this waveform line structure does not exhibit the usual edge effect, that is the sharp intensity bloom at an edge.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike a sharp-edged trapezoidal line structure, the SEM linescan profile of this waveform line structure does not exhibit the usual edge effect, that is the sharp intensity bloom at an edge. However, one can still characterize such a wave structure by the side effects to obtain the structure feature parameters such as peak height, width, and tilt angle [46].…”
Section: Introductionmentioning
confidence: 99%
“…31–36 Simulation results were found to be in good agreement with experiments. 37–42 By combining Mott's cross section for describing the electron elastic scattering and the dielectric function for the electron inelastic scattering, we have developed and applied classic trajectory Monte Carlo (CTMC) simulation models to SEM, 43–52 AES 53–56 and reflected electron energy loss spectroscopy 57–64 with different simulation codes. 65 This CTMC simulation approach has also been applied to the analysis of thin film nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…66–68 Even though one of the most significant advantages of the MC simulation method is on easy handling of complex sample geometrical boundaries, the previous Monte Carlo simulations have been mostly performed for simple and regular sample geometries until the applications of various numerical methods to the construction of the material interfaces. 47,49,51,52,69–74 For our present purpose it is necessary to apply these geometry construction methods to real-world nanomaterial morphologies for more comprehensive XPS analyses. Powell et al have used the simulation of electron spectra for surface analysis (SESSA) software, 27,28 where the sample structure was created with the PENGEOM geometry package, which uses analytic quadric surfaces to construct a NP morphology.…”
Section: Introductionmentioning
confidence: 99%